Синее, голубое, черное: палитра Владимира Эрля - Stratanovskij, Sergej (Wiener Slawistischer Almanach, 2024)
The article deals with one of the aspects of the work of Vladimir Ibragimovich (Ivanovich) Erl′, an outstanding representative of Leningrad unofficial literature, namely colouristics. The author of the article substantiates the application of this art history term to poetry and considers various contexts in which colours in Erl′’s poems appear. Particular attention is paid to blue, blue, and black as the main colours on the poet’s “palette”.